Effect of Metal Coating on Displacement of the Silicon Electrothermal V-Shaped Actuator - Fengqi Dai; Shuangjie Liu; Yongping Hao; Fengli Liu (Machines, 2023)
Electrothermal actuation is widely employed in MEMS systems, and the electrothermal V-shaped actuator (referred to as EVA) has garnered attention due to its stable output force. However, current EVAs in MEMS face the challenge of limited driving displacement. To investigate the impact of metal coating on the driving displacement of silicon EVAs, a mechanical model is established, and a formula for calculating the maximum displacement is derived. The theoretical analysis results are compared between cases with and without metal coating. To validate the formula’s accuracy, the COMSOL simulation platform is utilized, employing the finite element method to model and simulate actuators with various metal coatings. The analysis demonstrates that the calculated results have a maximum error of 10% compared to the simulation results. The metal coating enhances the displacement of silicon EVAs to different degrees, with a more pronounced effect observed for metal coatings with lower resistivity. Notably, a copper metal coating doubles the displacement of silicon EVAs at a voltage of 4 V. In other words, under the same displacement, a silicon EVA with a metal coating requires a lower input voltage compared to the group without a metal coating, resulting in a significant voltage reduction of 33.75%.